2021
DOI: 10.3390/molecules26082210
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Phytochemicals Derived from Avicennia officinalis for the Management of COVID-19: A Combined In Silico and Biochemical Study

Abstract: The recent coronavirus disease 2019 (COVID-19) pandemic is a global threat for healthcare management and the economic system, and effective treatments against the pathogenic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus responsible for this disease have not yet progressed beyond the developmental phases. As drug refinement and vaccine progression require enormously broad investments of time, alternative strategies are urgently needed. In this study, we examined phytochemicals extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…Although drug research has indicated a high level of interest in the investigation of natural products, realistically, the synthesis and purification of vast arrays of new compounds represent a research bottleneck [ 74 ]. To compensate for the time-consuming and costly nature of new product development, high-throughput screening techniques have been developed as effective methods for the identification of new hit compounds [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although drug research has indicated a high level of interest in the investigation of natural products, realistically, the synthesis and purification of vast arrays of new compounds represent a research bottleneck [ 74 ]. To compensate for the time-consuming and costly nature of new product development, high-throughput screening techniques have been developed as effective methods for the identification of new hit compounds [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization declared coronavirus disease 2019 (COVID-19) as a pandemic on March 11, 2020. The situation is deteriorating by increasing the daily infection and mortality rates [2] . The government of Bangladesh imposed a country-wide lockdown on March 26, 2020, to curb the spreading of the virus.…”
Section: Data Descriptionmentioning
confidence: 99%
“…This lower RMSD trend among the all seven complexes indicated the conformational stability of the docked and control complexes. Therefore, upon peptide binding with the target protein of SARS-CoV-2, lower degree of conformational variation was observed as all of the complexes were found rigid in dynamic simulation (Nainu et al, 2020;Rakib et al, 2020a;Rakib et al, 2020b;Rakib et al, 2020c;Tallei et al, 2020;Harapan et al, 2021;Mahmud et al, 2021a). The solvent accessible surface area of the docked complexes was also analyzed.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%